Non-intentionally added substances in food contact materials: how to ensure consumer safety. (December 2015) - Leeman, Winfried; Krul, Lisette
Highlights: Consumers may expect that their food including packaging materials is safe for use. For NIAS discussions on how to evaluate their safety is still ongoing. A pragmatic, scientifically valid safety assessment approach for NIAS is available. The priority setting using an exposure threshold efficient in NIAS safety screening. Exposure driven risk assessment prevents the performance of animal studies. Abstract : There is growing concern regarding the presence of non-intentionally added substances (NIAS) in food contact materials. These substances cannot be excluded from the food contact materials and end-up in our food. Identification thereof is often difficult or in some cases even not possible, which makes it difficult to evaluate their safety upon exposure. This review provides an overview of the current European Regulatory requirements and the latest innovations in the safety assessment of NIAS. Main conclusion is that recently an innovative, pragmatic and scientifically justified approach is published which can be used for prioritization of NIAS, based on their exposure and hazard.